Juridical Study of the Application of the Integrated Assessment Team (TAT) to Suspects Suspected of Narcotics Abusers at the National Narcotics Agency of Langkat Regency - Netty BR. Siahaan; Rahmayanti; Ismaidar (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the application of the Integrated Assessment Team (TAT) to suspects suspected of being narcotics abusers at the National Narcotics Agency (BNNK) of Langkat Regency from a juridical perspective. TAT is a mechanism formed based on Law Number 35 of 2009 concerning Narcotics, by involving medical and legal elements to provide recommendations for appropriate treatment for narcotics abusers. The procedure for implementing TAT starts from submitting an assessment application by investigators, administrative examinations, medical and legal assessments, to determining recommendations in the form of medical and social rehabilitation or follow-up legal processes. The results of the study show that the implementation of TAT at BNNK Langkat in general is in accordance with the provisions of the law, where most suspected narcotics abusers are recommended to undergo rehabilitation. However, several obstacles were still found, including the limitations of rehabilitation facilities, differences in perception between TAT elements, and public stigma against narcotics abusers. Therefore, the existence of TAT is very important to realize more humane, proportional, and fair law enforcement, while supporting rehabilitation efforts for narcotics abusers in Lalat Regency.